HEROINE AND PRINCESS: WOMEN IMAGE PORTRAYED IN SELECTED DISNEY’S STORIES - Resneri Daulay (Universitas Putera Batam, 2021)
The purpose of this study is to revealed the women image portrayed in selected Disney’s stories. There are several stories of Disney’s movie adaptation that are used as object in this research. There are Sleeping Beauty (Disney, 2014), Snow White (Brothers Grimm, 1812), Beauty and The Beast (Gabrielle-Suzanne Barbot, 1740), Cinderella (Giambattista Basile, 1634), Mulan (Guo Maoqian, 1992), and Brave (Disney, 2012). In addition, the aim of this research is also to identify the characteristics of female characters in selected Disney’s stories related to the Heroine and Princess attitude. This study used qualitative research; descriptive qualitative methods are used to analyze data. This study used three main concepts of semiotics theory by Roland Barthes, there are meaning of denotation, connotation, and myth. This study also applied feminism approach accordance to women attitude as heroine and princess. In this study, the researcher found some results. First, this study indicated the women image portrayed in Disney’s stories contains two images, they are women as heroine and princess. Women image as heroine is revealed in Beauty and the Beast, Mulan and Brave. Meanwhile, women as princess is portrayed in Sleeping Beauty, Snow White and Cinderella. Then, there are several characteristics found in Disney’s stories that represent the woman’s character as heroine and princess. They are from the feminism such as submissive, kind and gentle, domestic role, damsel in distress, emotional balance, craving for freedom (independent and brave), willing to sacrifice and has ability to stand up to the antagonist.